Interrogating Olu Amoda’s third eye: artist, poet and critic? (2015)
This essay explores the question of naming as a springboard for delving into some of the deeper issues of the process of artistic production as exemplified in the works of Olu Amoda, one of the most prominent producers of art in the Nigerian scene. It is a perennial issue in art history whether a work of art can stand meaningfully alone, or whether it requires a name for its meaning to become discernible, and for its identity to be established. This essay, from the standpoint of an insider engagement with the social and historical conditions that inform the naming strategies of the artist under study, puts forth the argument that artists have the ultimate responsibility to decide how to situate their works through naming, and that whether or not they situate their works through naming or titling, the works remain situated somewhat. For an artist like Olu Amoda, naming is a necessary part of the process of producing art. And in the classification of his works provided in this essay, it is demonstrated that similar strategies and concerns inform the decisions he makes in terms of selecting materials for producing his sculptures and in terms of naming the works he produces. In his use of naming strategies to locate his works, it is the same vision, the same third eye, that is in control.